Reasoning of parameters and operating conditions of direct stroke grain crusher - Yalpachyk, O.; Budenko, S. (My University, 2014)
This article provides basic results of theoretical and experimental studies of the cornmeal crushing process using the direct stroke grain crusher. On analyzing the current state of the problem, the conclusion had been made considering that one the ways to improve the crushing process is the grain crusher scheme implementation with the preliminary separation of the initial material and grinding each fraction at separate stages. The authors have developed the method and the instrument for crushing grain by the direct stroke of operating parts in the form of metal fingers with the preliminary separation of the grain material. Such a direct stroke grain crusher can be effectively used on small livestock farms. The article contains a description of the pin crusher prototype with the vertical axis of rotor rotation, being served as the basis for creating an experimental installation. Theoretical and experimental researches were carried out in order to set rational ratios of grain crusher designing parameters. Experimentally obtained regression equations, making it possible to determine the parameters of the given grain crusher type size, were described. The technique of forecasting energy costs when crushing grain material was developed, having made it possible to implement the forecasting of the efficiency rate and capacity of crushing the raw stuff, using the grain crusher. Experimental researches have clearly proved that the rational range of technological modes determined that the content of dust-like fraction in the ready-made product is 3…5 times less than while crushing at hammer crushers of other constructions. The specific energy consumption of crushing process in the direct stroke grain crusher is 1.8…2 times less than for other crushers.
Keywords: crushing; separation; grain; grain crusher